Pengaruh kewajiban kepemilikan NPWP, pemeriksaan pajak dan penagihan pajak dalam upaya peningkatan penerimaan pajak pada Kantor Pelayanan Pajak Pratama Kotamobagu - Roulani, Giroth Jessica; Kalangi, Lintje; Pinatik, Sherly (Indonesia Accounting Journal, 2020)
Taxes are a source of state revenue that is very important because it has a great influence on national development. To achieve the optimal tax revenue, countries need to implement various efforts through tax collection. This research aimed to determine the effect of ownership obligations taxpayer identification number, tax audit and tax collection in an effort to increase tax revenue. The Object of this research were tax officer at Kotamobagu Tax Office. The sampling method was used nonprobability sampling through purposive sampling technique with sample total are 30 person. The data analysis method was used multiple regression analysis. The results showed that the obligation of ownership Taxpayer Identification Number, tax audit and tax collection in partially did not effect in efforts to increase tax revenues, it can be seen from significant value of each variable is greater than 0,05.